Faktor yang Memengaruhi Minat Muzaki dalam Membayar Zakat Melalui Kitabisa.com: Pendekatan Technology Acceptance Model dan Theory of Planned Behavior - Astuti, Windi; Prijanto, Budi (AL-MUZARA'AH, 2021)
This study aims to examine the factors that influence muzaki's interest in paying zakat through Kitabisa.com with the Technology Acceptance Model and Theory of Planned Behavior approaches. In addition, this study analyzes the relationship pattern of the perceived usefulness, ease of use, attitudes, subjective norms, and behavioral control towards muzaki’s interest. The method used in this study is a quantitative method using Structural Equation Modeling (SEM). The analytical tool used is the SmartPLS version 3 software. The data collection technique was through distributing questionnaires with a total sample of 180 respondents. The results showed that muzaki’s interest in paying zakat through Kitabisa.com was influenced by perceptions of ease of use, attitudes, subjective norms, and perceptions of behavior control. This study proves that perceived ease of use has a significant effect on perceived usefulness. Perceived usefulness and perceived ease of use have a significant effect on attitudes. Meanwhile, perceived usefulness has no significant effect on the interest in using Kitabisa.com digital zakat services. In addition, perceptions of ease of use, attitudes, subjective norms, and perceptions of behavioral control have a significant effect on the interest in using Kitabisa.com digital zakat services.